ANALYSIS OF RELIGIOUS TOURISM VILLAGE DEVELOPMENT IN SELO VILLAGE, TAWANGHARJO DISTRICT GROBOGAN DISTRICT-CENTRAL JAVA - Malau, Natalia Artha; Tri Nur Hayati, Teguh Pamuji (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
This research aims to look at the development of a Religious Tourism Village in Selo Village, Tawangharjo District, Grobogan Regency, Central Java. This development is seen from economic, social and financial aspects. The results of this research are that the Selo Tourism Village has economic potential that is worth developing. Apart from that, there is support from the community and tourism actors in Selo Village to develop religious tourismKeywords: Development, Religious Tourism Village